Effect of Liquidity, Debt Policy, Company Growth, Board of Commissioners and Audit Committee on Dividend Policy - Pirdayanti, Putu Desy; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence regarding the effect of liquidity, debt policy, company growth, board of commissioners and audit committee on dividend policies of manufacturing companies listed on Indonesia Stock Exchange in 2013-2017. The method of determining the sample is using purposive sampling. The samples taken were 30 companies with 170 observations, by non-probability sampling method with purposive sampling technique. Data collected through non-participant observation.  Based on the results of research, debt policy and company growth have a negative effect on dividend policy, while liquidity, board of commissioners and audit committee have no significant effect on dividend policy. Keywords : Dividend policy, liquidity, debt policy, growth, board of commissioners, audit committee.